Potential use of selected antagonistic bacteria to control foot rot disease of black pepper (Piper nigrum L.) in Sarawak, Malaysia - Md Daut, Siti Noor Farhana (2014)
Black pepper (Piper nigrum L.) is one of high value export crops in Malaysia and this crop can easily been destroyedby pests and diseases. One of the most important diseases is foot rot disease which iscaused by Phytophthora capsici. Foot rot disease isthe most dangerous disease in black pepper and it is now become a major obstacle to the black pepper industry in Malaysia. Thus, the objectives of this study wereto survey the occurrence and distribution of foot rot disease in four major cultivation areas which are Sibu, Sarikei, Kapit and Bintulu in Sarawak, Malaysia. Secondly to isolate, identify and characterize P. capsici based on morphological and molecular methods. Lastly, to investigate the potential use of indigenous endophytic bacteria to control P. capsici under glasshouse condition. To achieve the first objective 13 survey areas in four major cultivating areas have been determined and conducted in between November 2010 to January 2011. Survey activity was conducted based on standard plant disease survey method. In study two, the causal pathogen and endophytic bacteria were isolated using standard isolation method. These isolates were then verified and characterized based on morphological and molecular characteristics. Finally, glasshouse study was conducted to assess the efficacy of potential endophytic bacteria to control P. capsici. Based on field survey data, infected plants normally exhibited symptoms of yellowingof leaves, leaves defoliationand wilting. High disease incidence and disease severity were recorded in all surveyed sites. The mean percentage for disease incidence anddisease severity were46.31 and 40.91%, respectively. P. capsici was successfully isolated using baiting method using rose bengal agar (RBA) and selective media, P5ARPH.The morphological characteristics of P. capsici were globose oogonia with paragynous antheridia, chlamydospore, torulose hyphae, and lemon shape of sporangia with long pedicels. In colony morphology, P. capsici showed very thick mycelia and formed multiple like a rosewhen growthon PDA media. Pathogenicity test wasfurther confirmed that the isolated fungus was pathogenic to black pepper plants. It was then further confirmed by nested-PCR using specific primer pairs of PC-1/PC-2. Antagonistic bacteria wassuccessfully isolated and screened. The potential of biocontrol agents were found to be able to induce systemic resistance in plants as well as showing biological control traits like producing antibiotic compounds which caused lysis to the phytopathogen cells. The use of antagonistic microorganisms should be preferable method because the biological control agents are internal colonizers and therefore more efficient to compete in the vascular systems. Thus, this will certainly deprive P. capsici in terms of nutrientsuptake and space for their proliferation. The three potential isolates known as BPA011, BPA040 and BPA025 were tested in-vitro showed high percentage of inhibition of radial growth (PIRG) which were81.40, 82.97 and 80.83%, respectively. These isolates were successfully identified using GC-FAME as Burkholderia cepacia, B. cenocepacia and Bacillus alchalapilus, respectively. Based on their colonization, establishment and localization ability in black pepper roots, B. cepacia and B. cenocepacia were selected for efficacy study in the glasshouse against Phytopthora foot rot in black pepper. Results revealed that they were able to suppress the growth of P. capsici compared to the control treatment. Besides delaying disease onset, they are also promoting the growth of the black pepper plant. Our study showed that disease incidence was significantly lower at 90 days after inoculation with B. cenocepacia (12.5%) and B. cepacia (18.75%). As expected positive control treatment presented the highest value of disease incidence (81.25%) at 90 days after inoculation. This indicated that B. cepacia and B. cenocepacia has a potential in controlling Phytophthora foot rot disease.